MEJORA DEL PERFIL DEL DOCENTE EN UNIVERSIDADES NACIONALES - Fairlie Frisancho, Ebor (2011)
This paperdefinesa proposal toraise the profileof university teachersbased on informationfrom otherLatin American countriesto improveeducationespecially inuniversitiesthat are inselfassessmentand accreditationoftheir careers andthat in someway or anotherrequire asubstantial changeto achieveinternational accreditation.